Eosinophilic Gastroenteritis: Case Report and Review in Search for Diagnostic Key Points - Guillermo López-Medina; Manuel Gallo; Alejandro Prado; Iliana Vicuña-Honorato; Roxana Castillo Díaz de León (Case Reports in Gastrointestinal Medicine)
Eosinophilic gastroenteritis is considered an uncommon disease with a low incidence rate that remains as a diagnostic challenge for the clinician, in spite of the fact that seventy years have passed since its original description. Hereby we present the case of a 29-year-old male without history of allergies who was evaluated for unspecific gastrointestinal symptoms, without relevant findings on physical examination and presenting an initial complete blood count (CBC) with severe eosinophilia. The patient was evaluated and the diagnosis of eosinophilic gastroenteritis was confirmed by histopathological findings. The relevance of the case resides in highlighting the lack of guidelines or consensus for histological diagnosis being virtually the only one available. To a similar extent, treatment evidence is based on case series with a reasonable number of patients and case reports.